Policy Response to International PhD Students' Mobility in France: Immigration, Europeanization, Internationalization - Alimukhamedov, Farkhad; Tõnismann, Teele (International Higher Education, 2024)
France, among top countries for doctorate abroad, grapples with labor market challenges for its 39 percent international PhD candidates. Despite alignment with EU’s strategies, disparities persist, because integration of international PhDs into the domestic labor market involves not only research and development but also migration policies. Policy analysts and decision makers must address this complexity for international PhDs, fostering diversity and knowledge-based economies in the EU and OECD.